2023
DOI: 10.1039/d3ra01276j
|View full text |Cite
|
Sign up to set email alerts
|

MXene-based composites against antibiotic-resistant bacteria: current trends and future perspectives

Abstract: This review endeavors to delineate critical issues pertaining to the application of MXene-based composites against antibiotic-resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…CB-2D-Ms can provide mechanical flexibility together with large surface area and pore size distribution. 14–25 Additionally, several studies have shown that CB-2D-Ms can effectively inhibit the growth of various bacteria, including Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ), and Pseudomonas aeruginosa ( P. aeruginosa ). Usually, their antibacterial activity can be attributed to various mechanisms, such as disruption of bacterial cell membranes, oxidative stress, and inhibition of bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…CB-2D-Ms can provide mechanical flexibility together with large surface area and pore size distribution. 14–25 Additionally, several studies have shown that CB-2D-Ms can effectively inhibit the growth of various bacteria, including Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ), and Pseudomonas aeruginosa ( P. aeruginosa ). Usually, their antibacterial activity can be attributed to various mechanisms, such as disruption of bacterial cell membranes, oxidative stress, and inhibition of bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Through the direct contact between MXene nanomaterials and microbes, the sharp edges in the MXene layered nanostructure penetrate and destroy the microbial cell membrane, causing microbial damage and eventual death. 91 Using scanning electron microscopy (SEM) and atomic force microscopy (AFM) imaging, Rasool and co-workers found that MXenes significantly damage the microbial membrane through direct physical contact. 92 Additional evidence for a direct physical interaction is obtained from growth curves of E. coli and B. subtilis in the presence of MXene nanosheets of different (lateral) sizes (0.09, 0.35, 0.57 and 4.40 μm).…”
Section: Antimicrobial Applications Of Mxene-based Materialsmentioning
confidence: 99%
“…MXenes have the potential to be a promising alternative to traditional antibiotics owing to their unique properties and potential applications in targeted drug delivery and non-invasive strategies against antibiotic-resistant pathogens. 40,41 MXenes employ three main mechanisms for exhibiting antibacterial activity: (a) inducing physical damage by sharp edges of MXene nanoflakes and direct mechanical destruction of bacterial cells, 42 (b) generation of reactive oxygen species (ROS), and (c) photothermal deactivation of bacteria (Fig. 2A).…”
Section: Mxenes Against Bacterial Infectionsmentioning
confidence: 99%
“…Thus, it is vital to gently consider the environmental impact of MXenes and their potential long-term effects on human health before widespread applications. 42,48…”
Section: Mxenes Against Bacterial Infectionsmentioning
confidence: 99%